A184 INCIDENCE OF VENOUS THROMBOTIC EVENTS AND RISK FACTORS IN CHILDREN HOSPITALIZED WITH INFLAMMATORY BOWEL DISEASE: A RETROSPECTIVE, CASE-CONTROL STUDY. (4th March 2021) - Ding, Z; Sherlock, M; Zachos, M
Abstract: Background: Limited research has been published to describe the incidence of venous thromboembolism (VTE) and relevant risk factors in Canadian children with inflammatory bowel disease (IBD). Aims: The present study aimed to investigate the incidence of VTE amongst hospitalized pediatric IBD patients over a 10-year period and identify risk factors for the development of VTE. Methods: A retrospective, matched case-control study was performed at McMaster Children's Hospital. Hospitalized pediatric patients with IBD (<18 years old) from September 2009 to August 2020 were selected. Inpatient data was extracted from the medical record database, including baseline demographic data, thromboembolic events and potential risk factors for VTE. Results: There were 890 hospitalizations of IBD patients during the study period. 15 (1.69%) were diagnosed with a VTE, including 4 males and 11 females (mean age 13.4±2.9 years old). 12 ulcerative colitis (UC) (80%) and 3 Crohn's disease (CD) (20%) hospitalizations were comprised in the VTE group. There was a significant difference in VTE rate between females (2.7%) and males (0.8%) ( P = 0.03). The VTE rate in the UC group (4.2%) was significantly higher than in the CD group (0.6%) ( P = 0.001). The incidence of VTE amongst hospitalized IBD patients did not vary over the 10-year period ( P = 0.496). Length of stay in hospital, albumin level and central venous catheter were shown to be significantly different, although they were not identified as independent risk factors ( P >0 .05). Of the 15 hospitalizations with VTE, 6/15 (40%) were superficial VTEs in the extremities and 9/15 (60%) had a deep vein thrombosis (DVT) including 6 in the extremities and 3 in the abdomen. VTEs were associated with a peripheral line in 7 patients and with a PICC line in 4 hospitalizations. 2 of 9 (22%) with extremity DVT developed symptomatic pulmonary embolism. An inherited thrombotic condition was identified in 2 of 15 with VTEs. 12/15 (80%) with VTEs were symptomatic and all VTE related symptoms happened in patients with extremity thrombosis and pulmonary embolism. 7 of 15 (47%) VTEs were treated with anticoagulation therapy for 1–6 months. VTE related symptoms and repeat imaging tests significantly improved, and no patient developed a bleeding complication as a result of treatment. Conclusions: The VTE rate in pediatric IBD patients was relatively low at McMaster Children's hospital. Children with VTE were disproportionately females with ulcerative colitis compared with children with no VTE. Central venous line insertion may be correlated with the risk for VTE in children with IBD. Most VTEs and related symptoms happened in patients with extremity thrombosis and secondary pulmonary embolus. Anticoagulation therapy in children with IBD with active disease appears to be safe. Funding Agencies: Kids Dig Health Funding from McMaster Children's Hospital, McMaster University